PENGGUNAAN GOOGLE CLASSROOM DENGAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS SISWA - Atiqoh, Khamida Siti Nur; Ranaista, Jihan Abiyyah; Musyrifah, Eva (ALGORITMA: Journal of Mathematics Education, 2023)
AbstractThis study aims to analyze the use of Google Classroom with Problem Based Learning model on students' mathematical representation abilities. This research was conducted at SMP Negeri 17 Tangerang Selatan City in the 2021/2022 academic year. The method used in this research is descriptive quantitative method, the test instrument has given in the form of 6 test items for mathematical representation ability and student response questionnaires in learning mathematics by Google Classroom with Problem Based Learning model. The research instrument was given to 78 students as research subjects. The results of this study are: the use of Google Classroom in learning mathematics with the Problem Based Learning model can be implemented by utilizing the features available in Google Classroom. The mathematical representation ability of students who learn by using Google Classroom with Problem Based Learning model as a whole is in the medium category. The positive response of students who learn mathematics using Google Classroom with Problem Based Learning model cumulatively 73.89% is in the high category. AbstrakPenelitian ini bertujuan untuk menganalisis penggunaan media Google Classroom dengan model Problem Based Learning terhadap kemampuan representasi matematis siswa. Penelitian ini dilakukan di SMP Negeri 17 Kota Tangerang Selatan pada tahun ajaran 2021/2022. Metode yang digunakan pada penelitian ini adalah metode deskriptif kuantitatif, instrumen tes yang diberikan berupa 6 butir soal tes kemampuan representasi matematis dan angket respon siswa terhadap pembelajaran matematika menggunakan Google Classroom dengan Model Problem Based Learning. Instrumen penelitian diberikan kepada 78 siswa sebagai subjek penelitian. Hasil penelitian ini yaitu penggunaan Google Classroom dalam pembelajaran matematika dengan model Problem Based Learning dapat diimplementasikan dengan memanfaatkan fitur-fitur yang ada pada Google Classroom. Kemampuan representasi matematis siswa yang belajar menggunakan media Google Classroom dengan model Problem Based Learning secara keseluruhan berada pada kategori sedang. Serta untuk respon positif siswa yang belajar matematika menggunakan Google Classroom dengan model Problem Based Learning secara kumulatif sebesar 73.89% berada pada kategori tinggi.